Experiences of people with stoma in the workplace (Estima – Brazilian Journal of Enterostomal Therapy, 2018)
Objectives: “To understand how the insertion in the work occurs after the intestinal stoma” and “to describe the diffi culties and facilities found by people with stoma in the work environment”. Method: Descriptive study, of a qualitative nature, performed with seven participants with defi nitive intestinal stoma. Data collection was realized in the Ostomy Patients Health Care Services of a municipality in Zona da Mata Mineira, in August 2014, using a semi-structured interview. In the analysis appeared three categories: the return to the workplace; the work and the person with stoma; diffi culties and facilities in the work environment. Difficulties identified: lack of adaptation of the environment to its new condition, embarrassment, physical weakness, fear of receptivity and insecurity regarding the condition of the person with stoma. Facilities mentioned: adaptation of toilets by some companies, reception of the employer and co-workers, company support and type of profession. Result: It has been demonstrated that the work for these individuals has important representativeness. They continued to feel useful and able to overcome the diffi culties imposed by the new reality. Conclusion: It is concluded that work is of paramount importance for the social reintegration of the person with stoma, and that nursing has a fundamental role in its adaptation and rehabilitation in the workplace.